Introduction to the Special Issue: Advances in island plant biology since Sherwin Carlquist's Island Biology. (18th August 2015) - Traveset, Anna; Fernández-Palacios, José María; Kueffer, Christoph; Bellingham, Peter J.; Morden, Clifford; Drake, Donald R.
Abstract : This is the introductory paper of the special issue emerging from the First Island Biology Symposium hosted in Honolulu on July 2014. The 18 papers compiled present data from multiple archipelagos across the world and from different disciplines within plant sciences, showing us how much island biology has advanced since Carlquist's inspiring contribution Island Biology . Such advance has been possible mostly thanks to the increasing availability and richness of island data, new information from the geosciences, phylogenetics, and palaeoecology, and new methodological advances in analyzing data at large spatial scales. A group of papers deal with issues to which Carlquist contributed most: long-distance dispersal, adaptive radiation, and plant reproductive biology, whereas others cover a range of topics related to plant conservation on islands. Abstract: Sherwin Carlquist's seminal publications—in particular his classic Island Biology, published in 1974—formulated hypotheses specific to island biology that remain valuable today. This special issue brings together some of the most interesting contributions presented at the First Island Biology Symposium hosted in Honolulu on 7–11 July 2014. We compiled a total of 18 contributions that present data from multiple archipelagos across the world and from different disciplines within the plant sciences. In this introductory paper, we first provide a short overview of Carlquist's life and work and then summarize the main findings of the collated papers. A first group of papers deals with issues to which Carlquist notably contributed: long-distance dispersal, adaptive radiation and plant reproductive biology. The findings of such studies demonstrate the extent to which the field has advanced thanks to (i) the increasing availability and richness of island data, covering many taxonomic groups and islands; (ii) new information from the geosciences, phylogenetics and palaeoecology, which allows us a more realistic understanding of the geological and biological development of islands and their biotas; and (iii) the new theoretical and methodological advances that allow us to assess patterns of abundance, diversity and distribution of island biota over large spatial scales. Most other papers in the issue cover a range of topics related to plant conservation on islands, such as causes and consequences of mutualistic disruptions (due to pollinator or disperser losses, introduction of alien predators, etc.). Island biologists are increasingly considering reintroducing ecologically important species to suitable habitats within their historic range and to neighbouring islands with depauperate communities of vertebrate seed dispersers, and an instructive example is given here. Finally, contributions on ecological networks demonstrate the usefulness of this methodological tool to advancing conservation management and better predicting the consequences of disturbances on species and interactions in the fragile insular ecosystems.